2019
DOI: 10.4067/s0719-81322019000100107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors, and identification of Salmonella spp. in stray dogs of northwest Mexico

Abstract: Salmonellosis has a worldwide relevance in aspects associated with public health, as only in 2009 were reported 93.8 million cases in humans. The objective of the study was to establish the prevalence, risk factors and bacteriological and molecular identification of Salmonella spp in stray dogs in urban, rural and coastal areas of Mexicali, a city in northwest Mexico. From May 2014 to February 2015, 385 dogs were tested. Sampling was performed by rectal swab and conventional bacteriological techniques were app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
3
3
Order By: Relevance
“…Furthermore, Sultan et al [ 38 ] and Kiflu et al [ 15 ] reported insignificant difference in the prevalence of Salmonella between age groups examined. In contrary to our finding, Núñez-Castro et al [ 61 ] from Mexico reported that dogs under 1 year are more likely to acquire Salmonella than dogs older than 1 year, while Zewdu et al [ 39 ] from Ethiopia reported that older dogs harbor more Salmonella than younger dogs. Often it is difficult to compare different findings, because different age profiles are seen in different studies and it is confounded by differences in sampled population lifestyles and owners dog caring practices.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Sultan et al [ 38 ] and Kiflu et al [ 15 ] reported insignificant difference in the prevalence of Salmonella between age groups examined. In contrary to our finding, Núñez-Castro et al [ 61 ] from Mexico reported that dogs under 1 year are more likely to acquire Salmonella than dogs older than 1 year, while Zewdu et al [ 39 ] from Ethiopia reported that older dogs harbor more Salmonella than younger dogs. Often it is difficult to compare different findings, because different age profiles are seen in different studies and it is confounded by differences in sampled population lifestyles and owners dog caring practices.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, the prevalence of Salmonella spp. in dogs was relatively higher than what was reported by Núñez Castro et al [34] (6.27%) and Bataller et al [35] (1.85%). The differences could be because both studies sampled healthy dogs, whereas, in this study, both healthy and unhealthy dogs were sampled.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, the prevalence of Salmonella spp. in dogs was relatively higher than what was reported by Núñez Castro et al [34] (6.27%) and Bataller et al [35] (1.85%).…”
Section: Discussioncontrasting
confidence: 59%
“…Results concurred with another study reporting the isolation of Salmonella Choleraesuis ssp. arizonae from stray dogs in urban areas of Northwest Mexico [40]. These observations underline that dogs serve as reservoirs of virulent Salmonella that can spread to other animals as well as humans.…”
Section: Discussionmentioning
confidence: 99%